Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa SMA Melalui Pembelajaran Open-Ended Pada Materi SPLTV - Ikromi, Syaiful Lutfi (Jurnal Matematika, Statistika dan Komputasi, 2018)
Abstract This aim of this study is to descript mathematics thinking creative ability of high school students (SMA) through open ended problem learning of SPLTV. Type of this research is descriptive qualitative. The subjects of this research are the students of class XII SMA. The steps of the research are namely (1) orientation, (2) material supply, (3) giving and solving open ended problem, (4) presentation and (5) conclusion. The mathematics creative thinking ability consists of (a) fluency, ability of the student to give a right answer fluency, (b) flexibility, ability of the student for using various manners in problem solving, (c) novelty, ability of the student to give a new answer and different with other student. The results of this research, is that the students have ability of mathematics creative thinking. Keywords: creative thinking, open ended problem, SBLTV Abstrak Penelitian ini bertujuan untuk mendeskripsikan kemampuan berpikir kreatif matematis siswa SMA melalui pembelajaran open ended problem materi SPLTV. Jenis penelitian ini, yaitu deskriptif kualitatif. Subjeknya adalah siswa kelas XII SMA. Tahap pembelajaran dalam penelitian ini adalah (1) Orientasi, (2) pembekalan materi, (3) penyajian dan pengerjaan soal open ended, (4) presentasi, (5) kesimpulan. Kemampuan berpikir kreatif matematis siswa meliputi: (a) fluency, kemampuan siswa lancar dalam memberikan jawaban benar, (b) flexibility, kemampuan siswa dalam menggunakan berbagai cara penyelesaian masalah, (c) novelty, kemampuan siswa dalam memberikan jawaban yang baru dan berbeda dengan siswa lain. Penelitian ini hasilnya, bahwa siswa mempunyai kemampuan berpikir kreatif matematis. Kata kunci: berpikir kreatif, open ended problem, SPLTV